2022
DOI: 10.1038/s41598-022-22803-y
|View full text |Cite|
|
Sign up to set email alerts
|

Catalytic DxD motif caged in Asx-turn and Met–aromatic interaction attenuates the pathogenic glycosylation of SseK2/NleB2 effectors

Abstract: Pathogenic bacteria encode virulent glycosyltransferases that conjugate various glycans onto host crucial proteins, which allows adhesion to mammalian cells and modulates host cellular processes for pathogenesis. Escherichia coli NleB1, Citrobacter rodentium NleB, and Salmonella enterica SseK1/3 type III effectors fatally glycosyltransfer N-acetyl glucosamine (GlcNAc) from UDP-GlcNAc to arginine residues of death domain-containing proteins that regulate host inflammation, intra-bacterial proteins, and themselv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…However, Asx-turns are very often formed along a second secondary structure, mainly β-turn, providing a well-defined H-bond-driven intersected conformation referred to as Asx-β-turn . To date, the debate on which turn pre-exists, thus fostering the formation of the second, is still open . Nevertheless, recent in silico research has shown that Asx–Gly sequence in a small dipeptide model is able to induce type II′ β-turns independently .…”
Section: Introductionmentioning
confidence: 99%
“…However, Asx-turns are very often formed along a second secondary structure, mainly β-turn, providing a well-defined H-bond-driven intersected conformation referred to as Asx-β-turn . To date, the debate on which turn pre-exists, thus fostering the formation of the second, is still open . Nevertheless, recent in silico research has shown that Asx–Gly sequence in a small dipeptide model is able to induce type II′ β-turns independently .…”
Section: Introductionmentioning
confidence: 99%